Mengom Area Mamfe Division Transfer of, to Bamenda Division (Colonial Letters and the Contact of Knowledges, 1933)
This file contains colonial letters on transfer of Mengom Area, Mamfe Division to Bamenda Division
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; British Colonisation; Colonial Records; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies